Producción de plantas macrófitas: Alternativa para la depuración en humedales artificiales (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2012)
The study moved forward with constructed wetlands in the head office Usme of the University Antonio Nariño where three species of plants adapt themselves macrophytes (Rumex conglomerates, Bidens laevis, and Typha latifolia) and an ornamental species (Zantedeschia aethiopica) taken root in inert or average substrate of plastic support (MSP), thinks about how to verify the adaptation of this vegetable material to a completely aquatic system, increasing his radicular production and to foliate, so much as the aptitude to increase the specific area for the growth of biomovie. The protocol used for the spread of the species was based on the reproduction in vivo using vegetative parts. The adequacy of the vegetable material to the acuatic system needed design and construction of the constructed wetland, selection of the vegetable material, definitive plantation and works of handling. The experimental work demonstrated some physiological changes demonstrating adaptation superior to a highly saturated way. The emission of roots (especially in Bidens laevis and Zantedeschia aethiopica penetrating the inert substratum (MSP) it increased the production of egg yolks base them, therefore, his biomass radicular and to foliate. The handling of pruning two times per year, he makes use of the period of flowering as ornamental element and allows preserving the efficiency sewage treatment plant of the system.
Keywords: Wetlands vegetatiton; constructed wetlands; macropythes; Rumex conglomeratus; Bidens laevis; Typha latifolia; Zantedeschia aethiopica